2018
DOI: 10.1108/ijem-03-2017-0056
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of service quality in higher education – critical review (students’ perspective)

Abstract: Purpose The purpose of this paper is to review the dimensions of service quality used in different countries across the world, especially in the higher education sector. Design/methodology/approach Content analysis is used to get a comprehensive insight of the studies accumulated from some of the selected databases such as Emerald Insight, Ebsco ABI/inform, etc. All these studies are related to the measuring of service quality in higher education. Findings The result of this paper reveals that SERVQUAL is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 41 publications
2
36
0
8
Order By: Relevance
“…Perceived service quality has been defined as a cognitive process based on consumer perceptions of service attributes. Via a literature review of 44 papers on service quality in HE, Gupta and Kaushik (2018) found that the disconfirmation method was the most commonly employed approach for measuring service quality. Under this approach, perceived service quality is an attitude stemming from customers’ evaluation of various service quality dimensions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Perceived service quality has been defined as a cognitive process based on consumer perceptions of service attributes. Via a literature review of 44 papers on service quality in HE, Gupta and Kaushik (2018) found that the disconfirmation method was the most commonly employed approach for measuring service quality. Under this approach, perceived service quality is an attitude stemming from customers’ evaluation of various service quality dimensions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Így, ha nincs megfelelő mennyiségű figyelem a nyújtott szolgáltatás értékelésén és a kapott eredmények elemzésén, elképzelhető, hogy a felsőoktatási intézmény minősége ún. hígul (Chung & McLarney, 2000;Zell, 2001;Ansary, Jayashree & Malarvizhi, 2014;Gupta & Kaushik, 2018). Ebben az esetben az intézmény nem képes elmozdulni a hivatali léttől és kihasználni szolgáltatásminőségének mértékét versenyképessége javításában (Demeter & Szász, 2012; Kenesei & Kolos, 2018).…”
Section: A Szolgáltatásminőség Mérése a Felsőoktatásbanunclassified
“…In order to gain competitive advantage in the fierce competition for students, HEIs are required to pay growing attention to provide the best possible service. In order to serve that need, they are forced to develop and manage a SQ assessment system (Gupta & Kaushik, 2018;Ansary et al, 2014;Chung & McLarney, 2000;Zell, 2001) utilizing institutional strengths.…”
Section: Stakeholders Of Higher Education Institutionsmentioning
confidence: 99%
“…Tóth et al, 2017). According to Gupta and Kaushik (2018), other key features should be highlighted as well; that is, higher education provides a unique service to each and every student, it has multiple stakeholders, it cannot be standardized and for most of the time HE does not aim at profit making. Stakeholders of the HE sector include undergraduate students, graduates, parents, university employees, labor market participants, funding bodies and foundations, scientific societies, government, society, etc.…”
Section: Stakeholders Of Higher Education Institutionsmentioning
confidence: 99%